The Relationship of VIX and Hedge Fund Returns - Keski-Marttunen, Mikael (My University, 2015)
This thesis studies the relationship between U.S. stock market uncertainty (VIX) and hedge fund returns during different economic states by using monthly data from January 2004 to April 2015. The crisis period is defined from August 2007 to March 2009. This paper examines five main hedge fund strategies and a total dataset constructed to reflect the whole hedge fund universe. The five strategies included are: Equity Hedge, Event-Driven, Macro, Relative Value and Emerging Markets. By using multivariate regression, this thesis reveals that there is a significant relationship between VIX and hedge fund returns indicating that VIX acts as an investor fear gauge not only for stock markets but for hedge funds as well. The test results indicate that there is a strong negative contemporaneous relation before, during and after crisis. This relationship is similar to S&P 500 which undermines the belief of hedge funds offering diversification benefits. This effect would appear to intensify during the crisis. Moreover, this relation would seem to last an additional month, implying deficiency in hedge fund managers’ information processing procedures. The Wald test results suggest that there is an asymmetric relationship between changes in VIX and hedge fund returns. Negative returns have a greater impact on volatility changes than positive ones, which can be explained by the elevated investor fear during the crisis. In addition, Granger causality tests suggest that changes in VIX have predictive power over short-term hedge fund returns for all strategies during crisis except Macro.
Keywords: Hedge fund; Performance; VIX; Financial crisis; Correlation; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|